2010
DOI: 10.1186/1743-422x-7-89
|View full text |Cite
|
Sign up to set email alerts
|

Fusion to chicken C3d enhances the immunogenicity of the M2 protein of avian influenza virus

Abstract: BackgroundCurrent vaccines to avian influenzae virus (AIV), a highly contagious disease of birds, need to be constantly updated due to the high level of variation in the target antigens. Therefore, a vaccine that could induce broad cross protection against AIV is required. The M2 membrane protein is structurally conserved amongst AIV subtypes but tends in induce a poor immune response, whereas C3d has been shown in many species to enhance immunogenicity. In this study, we investigated the potential of M2-avian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Combined with the positive vaccination experiments in chicken [22,23] this led to the expectation that M2 protein and M2e peptide vaccination would work in chicken as well. Our study shows that it is possible in chicken to raise antibodies against a bacterial expressed avian influenza M2 protein or streptavidin bound M2e peptide in a tetrameric conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with the positive vaccination experiments in chicken [22,23] this led to the expectation that M2 protein and M2e peptide vaccination would work in chicken as well. Our study shows that it is possible in chicken to raise antibodies against a bacterial expressed avian influenza M2 protein or streptavidin bound M2e peptide in a tetrameric conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al used a plasmid coding for an M2 protein of which the transmembrane region was deleted. They found that chicken C3d enhanced the humoral immunity against AIV M2 protein, be it with a poor protection ratio [22]. In contrast, Layton et al (2009) showed that Salmonella vectored vaccines expressing a M2e epitope in association with CD154 are effective at protecting chickens against LPAI, but not against HPAI [23].…”
Section: Introductionmentioning
confidence: 99%
“…ELISA titre was expressed as the end point serum dilution that gave an absorbance twofold higher than the value of rabbit pre-immune sera. 38…”
Section: Elisamentioning
confidence: 99%
“…Because there are receptors for C3d complement component (Li, et al, 2009, Zhang, et al, 2010, Zhang, et al, 2011 and domains 3 and 4 of Fc IgY (Taylor, et al, 2008, Purzel, et al, 2009) on dendritic cells, B lymphocytes and macrophages (antigen presenting cells (APC)), different gene segments such as four or eight repeats of 29 amino acids of C3d complement component (P29C3d) and domains 3 and 4 of the Fc part of IgY (FcIgY) were fused to hemagglutinin 9 (H9) gene in this study. Proteins encoded by DNA vaccines are targeted to the surface of APCs providing better importation into the APCs following likely better processing and more efficiency.…”
Section: Introductionmentioning
confidence: 99%